Naturally Acquired Bovine Besnoitiosis: Histological and Immunohistochemical Findings in Acute, Subacute, and Chronic Disease. (May 2015) - Langenmayer, M. C.; Gollnick, N. S.; Majzoub-Altweck, M.; Scharr, J. C.; Schares, G.; Hermanns, W.
The pathogenesis of bovine besnoitiosis, a disease of increasing concern within Europe, is still incompletely understood. In this study, disease progression after natural infection with the causative apicomplexan Besnoitia besnoiti was monitored in histological skin sections of 5 individual female cattle over time. High-frequency skin sampling of 2 cattle with mild and 2 with severe acute, subacute, and chronic besnoitiosis, as well as from 1 animal during subclinical disease, enabled documentation from the beginning of the disease. Skin sections were stained with hematoxylin and eosin and Giemsa, periodic acid–Schiff reaction, and anti- Besnoitia immunohistochemistry. In all 4 clinically affected animals, tachyzoite-like endozoites could be detected for the first time by immunohistochemistry, and tissue cyst evolution was monitored. Besnoitiosis-associated lesions were not detected in the animal showing the subclinical course. Because of the inconsistency of the nomenclature of Besnoitia tissue cyst layers in the literature, a new nomenclature for B. besnoiti cyst wall layers is proposed: tissue cysts consist of a hypertrophied host cell with enlarged nuclei, an intracytoplasmic parasitophorous vacuole with bradyzoites, a sometimes vacuolated inner cyst wall, and an outer cyst wall in more developed cysts. Inner and outer cyst walls can be readily distinguished by using special stains. In 1 animal, extracystic B. besnoiti zoites were immunohistochemically detected during the chronic stage. At necropsy, the 2 severely affected cows displayed large numbers of B. besnoiti cysts in a variety of tissues, including the corium of the claws, contributing mainly to the development of chronic laminitis in these 2 cases.